Antarctic Sea Ice, 1973-1976: Satellite Passive-Microwave Observations - Zwally, H. J.; Comiso, Josefino C.; Parkinson, Claire L.; Campbell, William J.; Carsey, Frank D. (1983)
This volume signals a striking step forward in both the technology of remote sensing of the Earth's environment from satellites and the provision of new and important geophysical data on the Antarctic. Furthermore, it again reminds us of the crucial role that the Antarctic plays as an indicator of climatic changes and as a crucial component of the system that determines our climate. I will briefly explain each of these points. The sea ice data from ESMR will be of interest to all those concerned with the Antarctic (or sea ice generally), from the navigators of ocean vessels who must penetrate the pack ice to climatologists seeking further clues to the heat balance of the Southern Hemisphere. The data are marvelously presented in the form of color-coded maps of the Antarctic and the southern oceans that show brightness temperatures and concentrations of pack ice, averaged for each month, 4-year monthly averages, month-to-month changes, and so forth. There are also graphs summarizing the results, such as areas of sea ice as a function of time in the various sectors of the southern ocean. The text explains in detail how this marvel of computer- drawn graphics was achieved, although the authors are modest in glossing over the enormous effort required to perfect the computer software. Original contains color plates: All DTIC reproductions will be in black and white.